2017
DOI: 10.1186/s12929-017-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes inside the beta-globin gene: use as new biomarkers for beta-thalassemia prenatal diagnosis in north of Iran

Abstract: BackgroundBeta-thalassemia is common in the Mediterranean area as well as the Middle East and India. Official report in Iran revealed the average prevalence rate of carriers about 4%. More than 20 restriction fragment length polymorphisms (RFLPs) are known in the beta-globin gene cluster and used in the prenatal diagnosis (PND) services. Some of these locations may have low allele frequency and are not informative in the prenatal diagnosis. The current study aims to find new haplotypes and polymorphisms with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The strong linkage disequilibrium of beta gene cluster haplotypes with prevalent mutations has been reported previously 20 - 22 . In our population, c.315+1G>A mutation is in linkage disequilibrium with haplotypes III (43.75%), I (31.25%), VII (20%), and IV (5%), respectively .…”
Section: Discussionmentioning
confidence: 68%
“…The strong linkage disequilibrium of beta gene cluster haplotypes with prevalent mutations has been reported previously 20 - 22 . In our population, c.315+1G>A mutation is in linkage disequilibrium with haplotypes III (43.75%), I (31.25%), VII (20%), and IV (5%), respectively .…”
Section: Discussionmentioning
confidence: 68%
“…Beside, four intragenic polymorphisms (C2(T > C), IVS‐II‐16(G > C), IVS‐II‐74(T > G), and IVS‐II‐666(C > T)) have been identified, which define three Frameworks. Framework identification could be used as an indirect method in prenatal diagnostic programs to track variant alleles and thus differentiate between normal and mutant alleles (Akhavan‐Niaki et al, 2012 ; Hashemi‐Soteh et al, 2017 ). Furthermore, two other polymorphisms at the UTR region (3′UTR + 34(C > A) and 3′UTR + 101(G > C)) were found.…”
Section: Discussionmentioning
confidence: 99%
“…The novel haplotype constructed in this study may provide a better representation of the actual genetic background of these mutations than those previously constructed. Previous β-globin gene haplotype studies have had the limitation of a recombination hot spot near the 5′ end of the β-globin gene, which may lead to mistakes in detecting mutated alleles [ 8 , 11 , 13 , 22 ]. To increase the accuracy of the indirect genetic background analysis, the evaluation of new polymorphic sites and molecular analysis of β-thalassemia are investigated [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two DNA polymorphisms on 3′ haplotypes are useful for studying the genetic background of β-globin genes: Ava II (IVS II-16) (rs10768683; C > G), located on the β-globin gene, and Hinf I (rs10837631; T > A), located on the 3′ β-globin gene [ 11 , 12 ]. Newly intragenic polymorphisms of the β-globin gene are informative polymorphisms in haplotype analysis associated with genetic background and clinical linkage studies of β-thalassemia mutations [ 13 , 14 , 15 ]. However, studies of these intergenic polymorphisms have yet to be comprehensively reported for the Thai population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%